P154 Evaluation of Inhaler Technique Mastery for Budesonide Formoterol Spiromax® Compared with Symbicort Turbohaler® in Adult Patients with Asthma: Primary Results From the Easy Low Instruction Over Time [ELIOT] Study. (12th November 2015) - Chrystyn, H; Dekhuijzen, R; Rand, C; Bosnic-Anticevich, S; Roche, N; Lavorini, F; Thomas, V; Steele, J; Raju, P; Freeman, D; Small, I; Canvin, J; et al.
Abstract : Introduction and objectives: Technical errors in the use of inhalers are associated with poor asthma control. This study evaluated achievement of mastery in a training environment using a randomised cross-over design (stage 1), followed by randomization into a prospective 12-week trial to assess maintenance of mastery in patients receiving inhaled corticosteroids (ICS)/long-acting β2 -agonists (LABA) via SPIROMAX versus ICS/LABA received via TURBOHALER (stage 2). Methods: Patients with asthma were randomised to a 6-step training protocol using empty Spiromax and empty Turbohaler devices. The proportion of patients achieving and maintaining inhaler mastery, respectively defined as the absence of health care professional (HCP)-observed errors by training step 3 (instructional video) in stage 1, and the absence of HCP-observed errors after 12 weeks of inhaler use in stage 2, were analysed using logistic regression. The maintenance of independent expert video-observed inhaler mastery was analysed using logistic regression. Total observed errors (HCP and technology) were analysed using a negative binomial regression model. Vitalograph Pneumatic Spirometry results were compared using a Mann Whitney U test. Results: A total of 493 (89.1%) patients (stage 1) and 305 (61.9%) (stage 2) were eligible for the full analysis set. The odds of maintaining inhaler mastery were not significantly different for patients using either inhaler, although achieving inhaler mastery was significantly greater in patients using Spiromax compared with Turbohaler at baseline. A higher, non-significant percentage of patients using Spiromax maintained inhaler mastery (assessed by HCPs). This result was supported by significantly higher odds of maintaining mastery when HCP errors were calibrated using independent video assessment in patients using Spiromax (consented videos available for 243/305 patients [79%]). Maintaining inhaler mastery improved asthma control in both treatment groups and was not significantly different (Table 1 ). Conclusions: The proportion of patients achieving inhaler mastery at baseline was significantly greater for Spiromax compared with Turbohaler; no significant difference was found in inhaler mastery at 12 weeks. Patients using Spiromax made significantly fewer errors overall (HCP-observed and HCP- and technology-observed) than patients using Turbohaler. Maintaining inhaler mastery improved asthma control in both treatment groups. Independent video assessment can assist HCPs in evaluating device mastery, and is proposed as the gold standard in such studies.